Preparation method of cobalt-molybdenum catalyst and application of cobalt-molybdenum catalyst in preparation of methyl mercaptan by hydrogenation of CO2 / H2S

The ternary oxide with a sheet-like morphology was synthesized by titanium modified hydrotalcite, and the surface was impregnated with molybdenum salt and potassium carbonate, followed by vulcanization treatment to obtain a cobalt-molybdenum catalyst, which solved the problem of low conversion rate of CO2/H2S hydrogenation to methylmercaptan catalyst in the prior art, and achieved efficient catalytic activity.

CN119702010AActive Publication Date: 2025-03-28FUZHOU UNIV

Patent Information

Application Number
CN202510002874.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

In the prior art, the conversion rate of CO2/H2S hydrogenation to methylmercaptan catalyst is low, making it difficult to effectively utilize polluted gases generated in the steel industry.

Method used

Titanium modified hydrotalcite is used as the precursor to synthesize ternary oxides with sheet-like morphology by hydrothermal method, and then soluble molybdenum salt and potassium carbonate are impregnated on the surface, and a cobalt-molybdenum catalyst is obtained by vulcanization treatment.

Benefits of technology

The activity of the H2S and CO2 hydrogenation to make methylmercaptan is improved. The catalyst has the characteristics of high dispersion and vacancies, which significantly improves the CO2 conversion rate and methylmercaptan yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702010A_ABST
    Figure CN119702010A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cobalt-molybdenum catalyst and application of the cobalt-molybdenum catalyst in preparation of methyl mercaptan through CO2 / H2S hydrogenation. According to the method, a titanium source is used as a modification additive, ethanol is used as a structure-directing agent, a hydrotalcite-like precursor with a sheet-like characteristic is synthesized by a simple hydrothermal method, and an active component is further loaded on the basis, so that the cobalt-molybdenum catalyst with high dispersion and rich vacancies is finally obtained. The titanium source is added, so that the density of electron cloud around the active component is increased, transferred electrons promote the strength of Mo-S bonds and Co-S bonds to be reduced, the Mo-S bonds and the Co-S bonds are easier to break to form sulfur defects, and adsorption and activation of CO2 and H2S are promoted. Meanwhile, due to injection of extra charges, MoS2 is induced to generate phase change from a 2H phase to a 1T phase, and the catalytic hydrogenation capacity of MoS2 in the reaction process is improved. Finally, the cobalt-molybdenum catalyst shows considerable catalytic activity in a reaction system for preparing methyl mercaptan through CO2 / H2S hydrogenation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation technology of an environmental catalyst and its application field, and in particular to the preparation of a cobalt-molybdenum catalyst and its application in the hydrogenation of CO2 / H2S to produce methyl mercaptan. Background Art

[0002] The steel industry produces a large number of byproducts and emissions during the production process, such as blast furnace gas, which contains a large amount of hydrogen sulfide (H2S) and carbon dioxide (CO2). How to effectively control H2S pollution and reduce CO2 emissions has become a problem that needs to be solved urgently.

[0003] Although H2S and CO2 are polluting gases, they can also be used as raw materials to prepare chemicals. Among various sulfur-containing compounds, methyl mercaptan, as a key fine chemical raw material and organic synthesis intermediate, plays an important role in the fields of pesticides, medicines and food synthesis, especially in the production of feed additive methionine. It is widely used and has high economic benefits (the market price is about 30,000 yuan / ton). The method of directly synthesizing methyl mercaptan using H2S and CO2 as raw materials can not only remove harmful H2S and CO2, but also obtain high-value-added products methyl mercaptan, realizing efficient utilization of resources. The key to this goal lies in the catalyst.

[0004] Based on this, the present invention discloses a preparation method of a cobalt-molybdenum catalyst and its application in CO2 / H2S hydrogenation to produce methyl mercaptan. Summary of the invention

[0005] The object of the present invention is to provide a preparation method and application of a cobalt-molybdenum catalyst in view of the deficiencies in the prior art, and solve the problems of low conversion rate of CO2 / H2S hydrogenation catalyst to methyl mercaptan in the prior art. The present invention adopts titanium-modified hydrotalcite as a precursor, and utilizes the flexible variability of its cationic valence state to transfer electrons to the active component, so that the electron density around it increases, the strength of Mo-S and Co-S bonds decreases, and the high dispersion of the active component is promoted and abundant sulfur defects are generated, thereby effectively improving the reaction activity of H2S and CO2 hydrogenation to methyl mercaptan. The catalyst with a flaky morphology can promote the full exposure of the active site, which is conducive to the full contact between the active site and the reactant. Sulfur vacancies can further promote the adsorption and activation of CO2 and H2S.

[0006] To achieve the above object, the present invention is implemented by the following technical solutions: A method for preparing a cobalt-molybdenum catalyst comprises the following steps: (1) Dissolve 50-500 μL of titanium source in 30 mL of anhydrous ethanol and stir for half an hour; (2) Dissolve 1-5 mmol of cobalt source, 1-5 mmol of aluminum source and 10-30 mmol of precipitant in 60 mL of deionized water; (3) After mixing the solutions obtained in steps (1) and (2), stirring was continued for half an hour; (4) pouring the mixed solution obtained in step (3) into a hydrothermal kettle and reacting at 120-150°C; (5) After the temperature of the hydrothermal autoclave drops to room temperature, the obtained precipitate is filtered, washed and placed in an oven for drying to obtain a modified ternary hydrotalcite precursor CoAlTi-LDH; (6) calcining the precursor obtained in step (5) at a certain temperature to obtain the ternary oxide CoAlTi-LDO; (7) The ternary oxide is impregnated with a soluble molybdenum salt and potassium carbonate by an equal volume impregnation method, and the cobalt-molybdenum catalyst is obtained by calcining and then sulfiding.

[0007] Preferably, the titanium source in step (1) is titanium tetrachloride (TiCl4) or tetraisopropyl titanate (C 12 H 28 O4Ti).

[0008] Preferably, the cobalt source in step (2) is Co(NO3)2·6H2O or CoCl2·6H2O, the aluminum source is Al(NO3)3·9H2O or AlCl3·9H2O, and the precipitant is urea.

[0009] Preferably, the reaction time in step (4) is 10 to 20 hours, preferably 12 hours.

[0010] Preferably, the filtering and washing in step (5) are performed by washing three times each with distilled water and anhydrous ethanol in turn.

[0011] Preferably, the drying temperature in step (5) is 80-100 °C.

[0012] Preferably, the calcination temperature in step (6) is 400-500°C, preferably 450°C, and the calcination time is 2-5 h, preferably 4 h.

[0013] Preferably, the soluble molybdenum salt in step (7) is ammonium heptamolybdate or ammonium tetramolybdate.

[0014] Preferably, the calcination temperature in step (7) is 400-500°C, preferably 400°C, and the calcination time is 2-5 h, preferably 2 h.

[0015] Preferably, in step (7), the sulfurizing gas is 10% H2S / H2, the sulfurizing temperature is 400°C, and the sulfurizing time is 8 hours.

[0016] Preferably, the final product, the cobalt-molybdenum catalyst, is sieved particles of 40-60 mesh.

[0017] An application of the cobalt-molybdenum catalyst prepared by the above preparation method: used for CO2 / H2S hydrogenation to produce methyl mercaptan.

[0018] Preferably, the reaction temperature for producing methyl mercaptan by hydrogenation of CO2 / H2S is 200-400°C, and the reaction pressure is 1.5 MPa.

[0019] Preferably, the amount of the cobalt-molybdenum catalyst is 1 g; the raw gas components and contents are calculated by volume percentage as follows: 4% H2S, 4% H2 and 1% CO2, with N2 as the balance gas; the raw gas flow rate is 5 mL·min -1 .

[0020] The present invention has the following advantages and beneficial effects: 1. The cobalt-molybdenum catalyst prepared by the present invention has the characteristics of uniform dispersion of active components and appropriate surface alkalinity, and the raw materials are cheap and the preparation process is simple, so it has broad application prospects; 2. The cobalt-molybdenum catalyst prepared by the present invention has abundant sulfur vacancies, which promotes the adsorption and activation of CO2 and H2S, and has good activity in the hydrogenation of CO2 / H2S to produce methyl mercaptan; 3. The present invention uses a titanium source as a modification additive and ethanol as a structure-directing agent to synthesize a hydrotalcite precursor with lamellar characteristics by a simple hydrothermal method, and further loads active components on this basis to finally obtain a highly dispersed, vacancy-rich cobalt-molybdenum catalyst. The addition of ethanol adjusts the growth direction of the hydrotalcite structure, forming a lamellar morphology that is conducive to the dispersion of active components and promoting the full exposure of active sites. The addition of a titanium source increases the electron cloud density around the active component, and the transferred electrons cause the Mo-S bond and Co-S bond strength to decrease, making it easier to break and form sulfur defects, promoting the adsorption and activation of CO2 and H2S. At the same time, due to the injection of additional charges, MoS2 is induced to undergo a phase transition from the 2H phase to the 1T phase, thereby improving its catalytic hydrogenation ability during the reaction process. Finally, the catalyst exhibits considerable catalytic activity in the reaction system of CO2 / H2S hydrogenation to methyl mercaptan. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 X-ray powder diffraction spectra of the hydrotalcite-like precursors prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 2 X-ray powder diffraction spectra of the multi-element oxides prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 3 X-ray powder diffraction spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 4The Raman spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 5 The EPR spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 6 The S 2p XPS spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 7 H2-TPR graphs of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Figure 8 The SEM images of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Fig. 9 TEM image of Example 1 of the present invention; Fig.10 The conversion rate of CO2 in the CO2 / H2S hydrogenation to methyl mercaptan reaction of the catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Fig.11 The selectivity of methyl mercaptan in the CO2 / H2S hydrogenation reaction to methyl mercaptan of the catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1; Fig.12 The yield of methyl mercaptan in the CO2 / H2S hydrogenation reaction of the catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in detail below in conjunction with embodiments and drawings. The examples described are further explanations of the present invention rather than limitations of the contents of the present invention.

[0023] Example 1 A method for preparing a cobalt-molybdenum catalyst: 165 μL of TiCl4 was dissolved in 30 mL of anhydrous ethanol and stirred for half an hour. 3 mmol of Co(NO3)2·6H2O, 1.5 mmol of Al(NO3)3·9H2O and 18 mmol of urea were dissolved in 60 mL of deionized water. After the above solutions were mixed, they were stirred for half an hour. Then the mixed solution was poured into a 150 mL hydrothermal kettle and reacted at 140 °C for 12 hours. After the temperature of the hydrothermal kettle dropped to room temperature, the precipitate was taken out, filtered, washed and placed in an 80 °C oven for drying to obtain a ternary hydrotalcite precursor named CoAl1Ti1-LDH, which was then calcined at 450 °C for 4 hours to obtain a ternary oxide named CoAl1Ti1-LDO. An aqueous solution containing 0.3066 g of ammonium heptamolybdate and 0.24 g of potassium carbonate was prepared by an equal volume impregnation method, and 1 g of the above ternary oxide carrier was added. After drying at 80 °C for 12 hours, it was placed in a muffle furnace and calcined at 400 °C for 2 hours. After cooling to room temperature, it was in-situ sulfurized at 400 °C in sulfide gas (10% H2S / H2 by volume) for 8 hours to obtain the final product named K2Mo / CoAl1Ti1-S.

[0024] Example 2 A method for preparing a cobalt-molybdenum catalyst: 82 μL of TiCl4 was dissolved in 30 mL of anhydrous ethanol and stirred for half an hour. 3 mmol of Co(NO3)2·6H2O, 2.25 mmol of Al(NO3)3·9H2O and 18 mmol of urea were dissolved in 60 mL of deionized water. After the above solutions were mixed, they were stirred for half an hour. Then the mixed solution was poured into a 150 mL hydrothermal kettle and reacted at 140 °C for 12 hours. After the temperature of the hydrothermal kettle dropped to room temperature, the precipitate was taken out, filtered, washed and placed in an oven at 80 °C for drying to obtain a ternary hydrotalcite precursor named CoAl3Ti1-LDH, which was then calcined at 450 °C for 4 hours to obtain a ternary oxide named CoAl3Ti1-LDO. An aqueous solution containing 0.3066 g of ammonium heptamolybdate and 0.24 g of potassium carbonate was prepared by an equal volume impregnation method, and 1 g of the above ternary oxide carrier was added. After drying at 80 °C for 1 hour, it was placed in a muffle furnace and calcined at 400 °C for 2 hours. After cooling to room temperature, it was in-situ sulfurized at 400 °C in sulfide gas (10% H2S / H2 by volume) for 8 hours to obtain the final product named K2Mo / CoAl3Ti1-S.

[0025] Example 3 A method for preparing a cobalt-molybdenum catalyst: 220 μL of TiCl4 was dissolved in 30 mL of anhydrous ethanol and stirred for half an hour. 3 mmol of Co(NO3)2·6H2O, 1 mmol of Al(NO3)3·9H2O and 18 mmol of urea were dissolved in 60 mL of deionized water. After the above solutions were mixed, they were stirred for half an hour. Then the mixed solution was poured into a 150 mL hydrothermal kettle and reacted at 140 °C for 12 hours. After the temperature of the hydrothermal kettle dropped to room temperature, the precipitate was taken out, filtered, washed and placed in an 80 °C oven for drying to obtain a ternary hydrotalcite precursor named CoAl1Ti2-LDH, which was then calcined at 450 °C for 4 hours to obtain a ternary oxide named CoAl1Ti2-LDO. An aqueous solution containing 0.3066 g of ammonium heptamolybdate and 0.24 g of potassium carbonate was prepared by an equal volume impregnation method, and 1 g of the above ternary oxide carrier was added. After drying at 80 °C for 12 hours, it was placed in a muffle furnace and calcined at 400 °C for 2 hours. After cooling to room temperature, it was in-situ sulfurized at 400 °C in sulfide gas (10% H2S / H2 by volume) for 8 hours to obtain the final product named K2Mo / CoAl1Ti2-S.

[0026] Comparative Example 1 A method for preparing a cobalt-molybdenum catalyst: 3 mmol of Co(NO3)2·6H2O, 3 mmol of Al(NO3)3·9H2O and 18 mmol of urea are successively dissolved in a mixed solution containing 30 mL of anhydrous ethanol and 60 mL of deionized water, and stirred for half an hour. Then, the mixed solution is poured into a 150 mL hydrothermal kettle and reacted at 140 °C for 12 hours. After the temperature of the hydrothermal kettle drops to room temperature, the precipitate is taken out, filtered, washed and placed in an 80 °C oven for drying to obtain a binary hydrotalcite precursor named CoAl-LDH, which is then calcined at 450 °C for 4 hours to obtain a binary oxide named CoAl-LDO. An equal volume impregnation method is used to prepare an aqueous solution containing 0.3066 g of ammonium heptamolybdate and 0.24 g of potassium carbonate, and 1 g of the above binary oxide carrier is added. After drying at 80 °C for 12 hours, it was placed in a muffle furnace and calcined at 400 °C for 2 hours. After cooling to room temperature, it was in-situ sulfurized at 400 °C in sulfide gas (10% H2S / H2 by volume) for 8 hours to obtain the final product named K2Mo / CoAl-S.

[0027] X-ray powder diffraction (XRD): The phase characterization of the samples was measured using the X'pert pro powder diffractometer from Panalytical, with an X'celerator as the detector, a copper target (Cu Kα, λ = 0.154 nm) as the excitation radiation source, an operating voltage of 45 KV, and an operating current of 40 mA.

[0028] Raman spectroscopy: The structural information of the samples was analyzed by in Via Reflex Raman spectrometer (RENIS-HAW, UK). The scanning range was 300~2500 cm –1 , the excitation light source was λ = 325 nm, the exposure time was 2-10 s, the laser intensity was 1%, and the number of scans was 6 times.

[0029] Electron paramagnetic resonance spectroscopy (EPR): The defect or sulfur vacancy information of the sample can be obtained by using an EPR200M electron paramagnetic resonance instrument (domestic). The test is carried out at low temperature and the test frequency is 100 kHz. After the sample is placed in a quartz tube, the tube should be kept vertical, and the working environment of the instrument should be stable and the air should be ventilated.

[0030] X-ray photoelectron spectroscopy (XPS): EscaLab 250Xi spectrometer was used to analyze the elemental composition and chemical state of the catalyst surface. The excitation light source was Al target Kα ray, and the vacuum degree of the analysis chamber was <10 -8 bar, the excitation power was 22.5 W, and the binding energy of C 1s at 284.8 eV was used for calibration.

[0031] H2-TPR: The reduction performance of the samples was analyzed by AutoChem 2920II chemical adsorption instrument. 100 mg of the catalyst was loaded into a U-shaped quartz tube and pretreated at 300 °C for 60 minutes under argon (30 mL / min). After cooling to room temperature, the temperature was raised to 900 °C (10 °C / min) under 10% H2 / Ar atmosphere for the reduction process, and the reduction signal was recorded by the TCD detector.

[0032] Field emission scanning electron microscopy (SEM): The morphology of the catalyst was observed using an S-4800 field emission scanning electron microscope. The vacuum degree of the analysis chamber was less than 2.7×10 –6 Pa, the scanning voltage and current were 5 kV and 7 μA respectively. The sample powder was glued to the conductive glue and then observed after gold spraying.

[0033] Field emission transmission electron microscopy (TEM): TEM images of the samples were observed on a Tecnai G2 F20 transmission electron microscope with an accelerating voltage of 200 KV.

[0034] Figure 1The X-ray powder diffraction spectra of the hydrotalcite-like precursors prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are shown in the figure. As can be seen from the figure, the four samples all have diffraction peaks at 11.7, 23.6, 34.6, 39.3, 47.0 and 60.3°, which are respectively attributed to the (003), (006), (012), (015), (018) and (110) crystal planes of the hydrotalcite-like precursors, indicating that the prepared precursors are all hydrotalcites.

[0035] Figure 2 The X-ray powder diffraction spectra of the multi-element oxides prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are shown in the figure. As can be seen from the figure, all four samples show the diffraction peak of Co3O4, and no characteristic peak of Al2O3 is observed, indicating that it exists in an amorphous form. In the samples after adding the titanium source, the (101) crystal plane diffraction peak belonging to TiO2 appears at 25.3°, indicating that titanium exists mainly in the form of titanium dioxide.

[0036] Figure 3 The X-ray powder diffraction spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1. As can be seen from the figure, all four samples show characteristic peaks of Co9S8 (JCPDS 65-1765) and Co3S4 (JCPDS 42-1448), indicating that molybdenum and cobalt are mainly present in the form of sulfides. Among them, the characteristic peak of the (002) crystal plane belonging to MoS2 (JCPDS 37-1492) is shifted to about 9.0°, which indicates the formation of 1T phase MoS2.

[0037] Figure 4 The Raman spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are shown in the figure. It can be seen from the figure that MoS2 and CoS x A 1g vibration mode, and the J1, J2 and J3 vibration modes of 1T-MoS2 exist, indicating that the catalyst CoS x Coexistence with MoS2.

[0038] Figure 5 The EPR spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are shown in FIG. As can be seen from the figure, all four samples have a certain amount of sulfur vacancies. By comparing the peak intensities, it is found that the modification of titanium can effectively increase the sulfur vacancy concentration of the catalyst.

[0039] Figure 6 The S 2p XPS spectra of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are shown in the figure. It can be seen from the figure that four sulfur species exist in all four samples: S 2- (161.2 eV)、S - (161.9 eV)、SO3- (164.9 eV) and SO4 2- (168.2 eV). Compared with K2Mo / CoAl-S without titanium modification, the low-valent sulfur binding energy peaks of the other catalysts shifted to a lower level, indicating that sulfur vacancies are more easily generated after modification. The abundant sulfur vacancies can promote the adsorption and activation of H2S and CO2.

[0040] Figure 7 The H2-TPR graphs of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1. As can be seen from the figure, all four samples show two H2 reduction peaks, of which the reduction peak at around 200 to 400 °C is attributed to the reduction of unsaturated sulfur atoms adsorbed on sulfur vacancies, and the strength and position of the peak are related to the Mo-S bond strength. The peak at around 500 to 650 °C is attributed to MoS2 and CoS x The results show that the addition of appropriate titanium source can generate more sulfur vacancies and promote the production of more active components.

[0041] Figure 8 The SEM images of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 are shown. As can be seen from the images, the four samples all have the morphological characteristics of flake stacking.

[0042] Fig. 9 This is the TEM image of Example 1 of the present invention, which shows that it is a lamellar structure, and lattice fringes belonging to MoS2, Co3S4, Co9S8 and TiO2 can be observed from the image, respectively, proving that Co3S4, Co9S8 and MoS2 exist simultaneously in the prepared cobalt-molybdenum catalyst.

[0043] CO2 / H2S hydrogenation to methyl mercaptan performance test: The cobalt-molybdenum catalysts prepared in Examples 1 to 3 and Comparative Example 1 were used for the evaluation of CO2 / H2S hydrogenation to methyl mercaptan. The test conditions were as follows: the catalyst dosage was 1 g; the raw gas components and contents were calculated by volume percentage: 4% H2S, 4% H2 and 1% CO2, with N2 as the balance gas; the raw gas flow rate was 5 mL·min -1 ; Reaction temperature is 200~400 ℃; Reaction pressure is 1.5MPa.

[0044] Figures 10-12 The activity results of the cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 in the CO2 / H2S hydrogenation to methyl mercaptan reaction are shown in Table 1. Compared with the catalyst without adding a titanium source, the modified cobalt-molybdenum catalyst has a higher CO2 conversion rate and methyl mercaptan yield due to the generation of more sulfur vacancies.

[0045] Table 1 Activity test results of cobalt-molybdenum catalysts prepared in Examples 1 to 3 of the present invention and Comparative Example 1 In summary, the cobalt-molybdenum catalyst prepared by the present invention has considerable catalytic performance in the CO2 / H2S hydrogenation reaction to produce methyl mercaptan, among which the K2Mo / CoAl1Ti1-S sample has the highest catalytic activity.

[0046] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a cobalt-molybdenum catalyst, characterized in that: The following steps are involved: (1) Dissolve 50-500 μL of titanium source in 30 mL of anhydrous ethanol and stir for half an hour; (2) Dissolve 1-5 mmol of cobalt source, 1-5 mmol of aluminum source and 10-30 mmol of precipitant in 60 mL of deionized water; (3) After mixing the solutions obtained in steps (1) and (2), stirring was continued for half an hour; (4) pouring the mixed solution obtained in step (3) into a hydrothermal kettle and reacting at 120-150°C; (5) After the temperature of the hydrothermal autoclave drops to room temperature, the obtained precipitate is filtered, washed and placed in an oven for drying to obtain a modified ternary hydrotalcite precursor; (6) calcining the precursor obtained in step (5) at a certain temperature to obtain a ternary oxide; (7) Soluble molybdenum salt and potassium salt are impregnated on the ternary oxide by an equal volume impregnation method, and the cobalt-molybdenum catalyst is obtained by calcining and then sulfiding.

2. The method for preparing a cobalt-molybdenum catalyst according to claim 1, characterized in that: The titanium source in step (1) is titanium tetrachloride or tetraisopropyl titanate.

3. The method for preparing a cobalt-molybdenum catalyst according to claim 1, characterized in that: In step (2), the cobalt source is Co(NO3)2·6H2O or CoCl2·6H2O, the aluminum source is Al(NO3)3·9H2O or AlCl3·9H2O, and the precipitant is urea.

4. The method for preparing a cobalt-molybdenum catalyst according to claim 1, characterized in that: The reaction time in step (4) is 10 to 20 hours.

5. The method for preparing a cobalt-molybdenum catalyst according to claim 1, characterized in that: The drying temperature in step (5) is 80-100°C.

6. The method for preparing a cobalt-molybdenum catalyst according to claim 1, characterized in that: In step (6), the calcination temperature is 400-500°C and the calcination time is 2-5 h.

7. The method for preparing a cobalt-molybdenum catalyst according to claim 1, characterized in that: The soluble molybdenum salt described in step (7) is ammonium heptamolybdate or ammonium tetramolybdate, and the potassium salt is potassium carbonate.

8. The method for preparing a cobalt-molybdenum catalyst according to claim 1, characterized in that: The calcination temperature in step (7) is 400-500°C, and the calcination time is 2-5 h.

9. A cobalt-molybdenum catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the cobalt-molybdenum catalyst according to claim 9 in the preparation of methyl mercaptan by hydrogenation of CO2 / H2S, characterized in that: When used for CO2 / H2S hydrogenation to methyl mercaptan, the reaction temperature is 200~400 ℃, the reaction pressure is 0~1.8 MPa; the raw gas composition is calculated by volume percentage: 1% CO2, 4% H2S, 4% H2, N2 is the balance gas, and the raw gas flow rate is 5 mL·min -1 ; The catalyst dosage is 1 g.

Citation Information

Patent Citations

  • Conversion of biomass or residual waste material to biofuels

    CA2937181A1

  • Process for the preparation of methyl mercaptan

    CN112041299A

  • Catalyst for synthesizing methyl mercaptan from carbon dioxide, hydrogen sulfide and hydrogen as well as preparation method and application of catalyst

    CN114308080A

Cited By

  • Preparation method and preparation device of mercaptan

    CN121202739A

  • Process for preparing mercaptans and apparatus therefor

    CN121202739B